The Educational Policy of Julian the Apostate - Csízy, Katalin (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
Julian the Apostate, the last pagan ruler of the Roman Empire has left a rich correspondence, the content of which is extremely varied. The epistles, most of which are authentic, form a separate volume in the editions and can be divided into four groups. The first group consists of the so-called Gallic letters, the second group includes the letters of Illyria and Constantinople, the letters from Asia Minor form the third group. Finally, the letters written from Antioch complete the list. In the following, we will discuss the School Edict and more particularly the letter that accompanies it (Ep. 61 Bidez – second group of letters). The decree of the Codex Theodosianus, dated 17 June 362, was rather short-lived, being in force only from July 362 to 11 January 364, but it is nevertheless an outstanding document of ancient educational history since no other emperor had previously issued similar regulations on the operation of teachers. Alongside this decree we may place the edict associated with Justinian (Cod. Just. I,5,18,4; I,11,10,2), which, conversely, forbids the pagan rhetors from education, but in the sixth century no one attempted to criticise it.